2021
DOI: 10.1101/2021.07.05.451107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

circFL-seq reveals full-length circular RNAs with rolling circular reverse transcription and nanopore sequencing

Abstract: Circular RNAs (circRNAs) act through multiple mechanisms with their sequence features to fine-tune gene expression networks. Due to overlapping sequences with linear cognates, identifying internal sequences of circRNAs remains a great challenge, which hinders comprehensive understanding of circRNA functions and mechanisms. Here, based on rolling circular reverse transcription (RCRT) and nanopore sequencing, we developed circFL-seq, a full-length circRNA sequencing method, to profile circRNA at the isoform leve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…2C). Since the performance of CIRI-full, a short read-based approach, for identifying full-length sequences of circRNAs is hampered by the length of short reads (Zheng et al 2019), we also extracted the full-length circRNA candidates identified by circFL-seq based on nanopore long reads (Liu et al 2021). Such a long read-based approach provided the direct support of full-length circular sequences from single-molecule long reads.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2C). Since the performance of CIRI-full, a short read-based approach, for identifying full-length sequences of circRNAs is hampered by the length of short reads (Zheng et al 2019), we also extracted the full-length circRNA candidates identified by circFL-seq based on nanopore long reads (Liu et al 2021). Such a long read-based approach provided the direct support of full-length circular sequences from single-molecule long reads.…”
Section: Resultsmentioning
confidence: 99%
“…For the most important factor in affecting circRNA reliability, since template switching events occur randomly during reverse transcription in vitro , a circRNA candidate observed in multiple samples or replicates is less likely to be generated from such an in vitro artifact. For the second most important factor in affecting circRNA reliability, full-length circular sequences can be reconstructed by Illumina short RNA-seq reads with the reverse overlap (RO) feature (Zheng et al 2019) or identified by single-molecule long reads (Liu et al 2021). With the support of RO-merged reads, the BSJ events are less probable to originate from template switching because both ends of the paired-end reads are sequencing from the same fragment and reversely overlapped with each other by alignment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with next‐generation sequencing, the optimized nanopore sequencing system and bioinformatics methods can greatly improve the detection efficiency and accurately quantify the expression of circRNAs. Moreover, nanopore sequencing can achieve the full sequence assembly of circRNAs with a length of 100 bp–5 kb [50–53]. Real‐time quantitative polymerase chain reaction and Northern blot are the primary methods used to analyze circRNA expression.…”
Section: Methods For Circrna Detectionmentioning
confidence: 99%
“…Moreover, PCR bias can lead to more efficient amplification of some circRNAs, additional events such as trans-splicing and exon repetitions further hamper identification of circRNA in the native form(13). Accordingly, the long-read sequencing technology has been applied to circRNAs only from reverse transcribed products (1416).…”
Section: Mainmentioning
confidence: 99%